The Art of Action - Martial Arts in Movies - Clarke, Keith; Finestone, Steven; Ang Lee; Woo, John; Samo Hung Kam-Bo (Columbia Tristar, 2002)
Trace the evolution of martial arts films and their spread around the world in this action-packed program hosted by Samuel L. Jackson. From rare silent-era clips and the earliest Hong Kong stars to today's Hollywood blockbusters, you'll see breathtaking fight scenes from "Rush Hour 2," "Crouching Tiger, Hidden Dragon," "The Matrix" and more, plus hear from such martial arts cinema notables as Jackie Chan, Sammo Hung, Donnie Yen, John Woo and others. [www.amazon.com]
Keywords: DVD-Video